Clinical value of drug-coated balloon angioplasty for de novo lesions in patients with coronary artery disease. (1st November 2016) - Nishiyama, Naoki; Komatsu, Takaaki; Kuroyanagi, Takanori; Fujikake, Akinori; Komatsu, Sachiko; Nakamura, Hidehiko; Yamada, Kota; Nakahara, Shiro; Kobayashi, Sayuki; Taguchi, Isao
Abstract: Background: Despite the low restenosis rates of drug-eluting stents (DES), several problems remain, including stent thrombosis, stent fracture, and neo-atherosclerosis. 'Stent-less' (balloon alone) percutaneous coronary intervention (PCI) is still being used, and several clinical trials have supported the efficacy of DCB. The aim of this study was to investigate the efficacy of a drug-coated balloon (DCB) in the treatment of de novo coronary artery disease. Methods: We enrolled 60 consecutive patients who had been given elective PCI between May 2014 and June 2015. They were randomly assigned to a 'stent-less' group (n = 30) and a 'stent' group (n = 30). Twenty-seven patients were treated with DCB alone and 33 with DES, and then evaluated for target lesion revascularization (TLR) rate and by quantitative coronary angiography (QCA) eight months later. Results: TLR rates were similar in the two groups (DCB; 0.0%, DES; 6.1%, P = 0.169). In the QCA analysis, minimal lumen diameter (MLD) and acute gain were significantly smaller in the DCB group than in the DES group immediately after PCI (2.36 ± 0.46 vs 2.64 ± 0.37, P = 0.011, and 1.63 ± 0.41 vs 2.08 ± 0.37, P < 0.0001, respectively). Eight months after PCI, however, there was no significant difference in MLD or late lumen loss between the two groups. Conclusions: A 'stent-less' PCI using DCB could be useful even in the DES era. After 'stent-less' PCI, antiplatelet agents might be reduced or discontinued more safely than after DES implantation.